Pengembangan Website Desa sebagai Proses Digitalisasi Informasi dan Mempromosikan Potensi Desa - Noviandari, Hanifah (MUJAHADA: Jurnal Pengabdian Masyarakat, 2023)
Undoubtedly, the independent management of the Ngunut Village website definitely provides convenience in optimizing information services and Ngunut's promotional potential. Therefore, community service is proposed, "Village Website Development as a Process of Digitizing Information and Promoting Village Potential." PAP (Project Action Plan) is the basis of the implementation method, which consists of the following stages: site survey, website creation, website management workshop, and a test method with four indicators. According to the survey, Ngunut has internet access, but no website. The results showed that the success rate in creating website views was 100%, and the participation rate in workshops was 86.7%. and the materials have been fully delivered. Furthermore, the results showed that the participants had a good ability to understand the material and complete the web content. Thus, these results show that the services provided can help village heads and villagers to be more proficient in reading and using technology to complete village web content independently.